“We are in this together” – distance learning experience in small schools in a pandemic in spring 2021 - Andl Helga; Laki Tamásné (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. In the past, some research summaries on the educational situation of small villages and small schools have been produced both in the international literature, such as those by Harrison and Busher (1995) and Fickermann et al (1998), and in Hungarian publications, such as those by Forray (1998, 2009), Imre (2009), Jankó (2011) and Andl (2020). Also, the digital curriculum introduced during the COVID19 epidemic, the implementation of online education, and the consequences of the transition or some aspects of the transition have been the subject of several studies in Hungary1 . Some of these studies emphasised aspects of equity (Hermann 2020; Kende et al. 2021), showing that the disadvantaged situation of the municipality and the high proportion of disadvantaged pupils (HH) and pupils with special educational needs (SNI) made it more difficult to reach pupils, and that the existing disadvantages of pupils were exacerbated. However, to our knowledge, the impact of the digital switchover process in small schools has not yet been studied on a national or international level. Our research, conducted in spring 2021 – when primary schools switched back to distance learning – aimed to explore the implementation of distance education methods in small schools in Baranya county with only lower (primary) grades based on interviews conducted with the heads of the researched institutions.
„Együtt toljuk a szekeret” – a kisiskolákban megvalósuló távolléti (digitális) oktatás a pandémia alatt 2021 tavaszán
Keywords: small school; small settlement; Covid –19-pandemic; online education; distance learning